Hubungan antara Pengetahuan dan Sikap dengan Perilaku Seksual Pranikah Siswa Kelas XI - Ni Kadek Lissa Arniyanti; Dwi Prima Hanis Kusumaningtiyas (Universitas Triatma Mulya, 2018)
Introduction. Data of the results of Indonesia Health Demographic Survey (2012) indicate that 29.5% of male adolescents and 6.2% of female adolescents have ever touched and sexually stimulated their partners and 48.1% of male adolescents and 29.3% had ever given their partners a lip kiss. In this survey the age of first dating is mostly 16-17 years old. This research is aimed at identifying the correlation of behavior and attitude with premarital sexual behavior of eleventh grade student at SMA Negeri I Depok Sleman Yogyakarta in 2015. Methods. This research is a correlational analytical research with cross sectional approach. The research population was the eleventh grade students. Sampling technique used proportional stratified sampling with a sample size of 125 students. Data were collected using questionnaires. The data were collected on 28029 May 2015. The data were analyzed using Chi Square and multiple correlations. Results. Knowledge mostly belonged to the sufficient category (73.6%), while attitude mostly belonged to the good category (94.4%) and premarital sexual behavior mostly belonged to the category of positive behavior (91.2%). There was a correlation between knowledge and premarital sexual behavior in which the value of Fisher’s Exact test was 0.024<0.05, while there was no correlation between attitude and premarital sexual behavior in which the value of Fisher’s Exact test was 0.484>0.05. There was simultaneous and significant correlation of knowledge and attitude with premarital sexual behavior, in which was the value of sig. FChange was 0.000<0.05. Conclusion. There is a correlation of behavior and attitude with premarital sexual behavior of eleventh grade student at SMA Negeri I Depok Sleman Yogyakarta in 2015.